Komparasi Rasio Profitabilitas Dan Likuiditas 2021-2022 Pada Perusahaan Emiten Unggas - Endhi Hermina Ayu; Kristian Aldion Bramanto; Sri Hermuningsih (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This research aims to identify and analyze the differences in profitability and liquidity ratios between PT Charoen Pokphand Indonesia Tbk and PT Japfa Comfeed Indonesia Tbk as poultry issuer companies for the period of 2021-2022. The research method applied is descriptive-comparative, involving the comparison of financial data from both companies for the years 2021 and 2022. Data were obtained from the financial performance reports published on the official website of the Indonesia Stock Exchange. The analysis technique includes calculating profitability ratios such as Return on Assets (ROA) and Return on Equity (ROE), as well as liquidity ratios such as Current Ratio (CR) and Quick Ratio (QR). The analysis results show that PT Charoen Pokphand Indonesia Tbk has a higher ROA than PT Japfa Comfeed Indonesia Tbk, although there was a decrease from 2021 to 2022 for both companies. Meanwhile, the comparison of ROE indicates fluctuation in financial performance between the two companies during the observed period. The liquidity analysis shows that both companies have CR above 1, but experienced a decrease from 2021 to 2022, while QR increased from 2021 to 2022. The decrease in ROA and ROE indicates challenges in asset efficiency and the companies' ability to generate net profit, while the increase in QR suggests improvement in the companies' ability to meet short-term financial obligations